Struktura fenomenalnega sveta in koncept nejaza v delu Vprašanja Kralja Milinde - Šumiga, Dražen (Monitor ISH, 2009)
The article discusses the question of the Self in early Buddhism. Outlining the structure of the phenomenal world and the notion of the Self, it asserts that the Self is no eternal substance underlying all psychic and physical events. Rather, the author agrees with the observation of Veljačić, who shows that Buddhist psychology, analysing the structure of the no-Self, arrives at the concept of a human being as a "moment" or a "situation". The article likewise touches upon an interesting analysis of the Self included in the Questions of King Milinda, where the reader is led to realise the insubstantial structure of the Self and of the World through a Socratic dialogue form.
Keywords: jaz; subjekt; Buddhism; budizem; Vprašanja kralja Milinde; epistemologija; epistemology